2022
DOI: 10.5530/ijper.56.1s.42
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro Evaluation of Anti-microbial and Cytotoxic Activity of Artemisia judaica Leaves and Stem Extracts via Induction of Caspase Dependent Apoptosis

Abstract: Medicinal plants and herbs are commonly used in the world to treat various human disorders. Artemisia judaica is one of these herbal species that is commonly used in medicine due to its contents of many bioactive compounds such as; flavonoids, lactones, essential oil and sesqui-terpenoids. It was used in many traditional medicines as an anthelmintic, antispasmodic, anti-rheumatic, and antibacterial agent. In recent years, anti-bacterial and anti-cancer activity of medicinal herbs are highly investigated. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Several studies have explored the antimicrobial properties of various Artemisia species, including Artemisia judaica, against different bacterial pathogens [18,31,32]. Some studies have reported similar findings, supporting the antibacterial efficacy of Artemisia judaica extract against pathogenic bacteria [33]. For example, a study on the antibacterial activity of Artemisia against a range of bacterial strains, including K. pneumoniae, was conducted and observed inhibition zones in agreement with the outcomes of the current study [34].…”
Section: Discussionsupporting
confidence: 84%
“…Several studies have explored the antimicrobial properties of various Artemisia species, including Artemisia judaica, against different bacterial pathogens [18,31,32]. Some studies have reported similar findings, supporting the antibacterial efficacy of Artemisia judaica extract against pathogenic bacteria [33]. For example, a study on the antibacterial activity of Artemisia against a range of bacterial strains, including K. pneumoniae, was conducted and observed inhibition zones in agreement with the outcomes of the current study [34].…”
Section: Discussionsupporting
confidence: 84%
“…The antiparasitic compounds from the Asteraceae family are described as sesquiterpenes, lactones, phenols as tannins or gallic acid [ 6 ]. The anthelmintic compounds described below are reported as members of the genus Artemisia [ 7 ]. Artemisia was used against Trypanosoma cruzi and Giardia lamblia infections in humans [ 8 ].…”
Section: Introductionmentioning
confidence: 99%